Evaluation Of The Design Of Auxiliary Equipment At The Back Printing Station With Ergonomic Approach - Fahmi Fathurrahman (IHSA Institute, 2020)
Ngatiyem refinery is a small and medium enterprise that produces bricks. This business was founded in 2005 which is located in Jatimulyo village, Perbaungan district, Deli Serdang regency, North Sumatra province. The process of making bricks is carried out for 8 hours every day with 12 workers and produces 15,000 bricks. The problem faced by the company is that activities at the printing station experience problems with working postures for operators who are not ergonomic so that it can cause MSDs, operators become tired quickly, complaints of work-related illnesses are high and errors often occur in work. The purpose of this research is to improve the facilities used in order to simplify and reduce existing obstacles. With the design of the tool design, it is expected to be able to overcome the problems faced by the company so that the products produced are getting better and increasing in quantity. The results of the REBA (Rapid Entire Body Assessment) data processing show that activities at the stone molding station must be repaired as soon as possible to reduce the existing problems.